Thickness and Evaluation - Eklund, Matti (Journal of moral philosophy, 2017)
This is a review essay devoted to Pekka Väyrynen’s The Rude, the Lewd and the Nasty. Väyrynen’s book, concerned with thick terms and thick concepts, argues for a pragmatic view on the evaluativeness associated with these terms and concepts. The essay raises a number of critical questions regarding what Väyrynen’s arguments for his view actually show. It deals with, for example, thick properties, the fact-value distinction, what it is for terms and concepts to be (semantically) evaluative, and whether Väyrynen’s arguments generalize to thin evaluative concepts.